Study of the effect of the introduction of Tris(bipyridine)ruthenium(II) chloride into silicon dioxide particles by spectrofluorometry methods - Irgibayeva, Irina; Mantel, Arthur; Barashkov, Nikolay; Lu, Olga; Yensebayeva, Akbota; Aldongarov, Anuar; Mendigaliyeva, Svetlana; Barashkova, Irina (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2021)
The Stoeber reaction was used to grow silica microparticles in the presence of the fluorescent dye Tris(bipyridine)ruthenium (II) chloride. The diameter of the obtained particles varies from about 150 to 280 nm depending on the dye concentration. Using spectrofluorometry methods, concentration quenching of fluorescence of dye solutions was studied before and after growing the microparticles. It was found out that the concentration quenching of fluorescence decreases significantly after its incorporation into the silicon dioxide microparticles upon excitation in the short-wavelength region of the spectrum.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Concentration quenching; Excitation spectra; Fluorescence spectra; Silica microparticles; Stoeber reaction; Tris(bipyridine)ruthenium (II) chloride